Intra-abdominal desmoid tumors in familial adenomatous polyposis: How much do clinical and surgical variables interfere with their development? (Clinics, 2022)
Objective: Familial Adenomatous Polyposis is a complex hereditary disease that exposes the carrier to a great risk of Colorectal Cancer (CRC). After prophylactic surgery, intra-abdominal desmoid tumors are known to be one the most important cause of death. Therefore, recognition of increased-risk patients and modification of operative strategy may be crucial.Aim: The objective of this study was to estimate the desmoid tumor risk in relation to various surgical and clinical variables.Methods: Patients who had undergone polyposis since 1958 were included in the study. After exclusion criteria were met, those who had developed desmoid tumors were selected to undergo further evaluation.Results: The study revealed that the risk of developing desmoid tumors was associated with various factors such as sex ratio, colectomy, and reoperations. On the other hand, the type of surgery, family history, and surgical approach did not affect the risk of developing desmoid tumors. The data collected from 146 polyposis patients revealed that 16% had desmoid polyps. The sex ratio was 7:1, and the median age at colectomy was 28.6 years. Family history, multiple abdominal operations, and reoperations were some of the characteristics that were common in desmoid patients.Conclusion: Recognition of clinical (female sex) and surgical (timing of surgery and previous reoperations) data as unfavorable variables associated with greater risk may be useful during the decision-making process.